THU0484 Impact of TNF Antagonists on the Joint Manifestations of Sarcoidosis. (23rd January 2014) - Banse, C.; Bisson-Vaivre, A.; Kozyreff-Meurice, M.; Dominique, S.; Vittecoq, O.; Goeb, V.
Abstract : Objectives: Use of anti-TNF agents to treat joint manifestations of sarcoidosis has not been described. We evaluated the efficacy and safety of 3 such biologics in patients with these symptoms refractory to conventional therapy (NSAIDs, corticosteroids and/or DMARDs). Methods: This retrospective study, covering January 2001 to September 2011, examined the following clinical–biological parameters collected before anti-TNF treatment (age, sex, duration of disease evolution, drugs taken), and at introduction and under anti-TNF therapy (number of painful and swollen joints, visual analogue-scale score of global disease activity, Disease Activity Score-28 with ESR or CRP, TNF-antagonist duration). At 3, 6 and 12 months, anti-TNF impact on joints and the therapeutic response according to EULAR criteria used for rheumatoid arthritis were assessed. Results: Ten patients data were evaluated; some of them had received several anti-TNF agents (median (range) duration on each biotherapy was 10 (4–30) months), which enabled analysis of 19 prescriptions. The total duration of anti-TNF exposure was 17.6 patient-years, that was started a median of 3 (0.33–17) years after sarcoidosis diagnosis. The median numbers of painful and swollen joints were, respectively, 1 (0–28) and 0 (0–9). Despite rapid efficacy, after 1 year of treatment, clinical (especially joint) and biological parameters were comparable to pretreatment and only the corticosteroid dose was significantly lower ( P = 0.03). One case of mild skin toxicity was noted. Conclusions: TNF antagonists allowed significant steroid-sparing and were well-tolerated but do not seem to be effective against sarcoidosis joint involvement. Disclosure of Interest: None Declared